PENGARUH PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Maliah Maliah; Sahila Sahila; Liliana Liliana (Universitas Tridinanti, 2022)
This study aims to determine the effect of Return on Equity (ROE) and Earning per Share (EPS) simultaneously on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX). The method used in this study is associative and uses a quantitative approach. The sample in this study is 43 banking companies listed on the Indonesia Stock Exchange in 2017-2019 (43x3=129 samples). The data analysis technique used in this research is descriptive statistics, normality test, classical assumption test, multiple linear regression, coefficient of determination, t test, f test using the software program spss 22 for windows. From the results of the t-test research shows that Return on Equity (ROE) has an effect on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) because the significant value is 0.006 <0.05. Earning per Share (EPS) has an effect on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) because the significant value is 0.000 <0.05. Return on Equity (ROE) and Earning per Share (EPS) have a simultaneous effect on stock prices in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) because the significant value is 0.000 <0.05.Keywords : Stock Price, Return on Equity and Earning per Share